STRATEGI PEMBERIAN BONUS KARYAWAN PABRIK KACA UNTUK MENINGKATKAN KINERJA KARYAWAN DENGAN METODE ANALYTIC NETWORK PROCESS (ANP) - Wina Yusnaeni (Jurnal Khatulistiwa Informatika, 2014)
Research is done to make a choice of an employee who is entitled to get a bonus with the methods anp, In which method is using the factor that there are companies, according to the terms of the criteria to look for the precedence of any criterion for determining criteria that is more important. So for every focusing only one criteria of judgment dominant.So that it can be used as a guideline to give judgment against the employee, For employees can motivate others to improve its performance. A decision can be taken based on the results of stimuli that respondents a questionnaire containing comparisons between the criteria and alternative as a test ( employees ) decision maker involved in its evaluation employees. Research methods used are questionnaire, librarianship, and respoden. Opinion of respondents very important in the provision of opinion calculating-wise priority cluster because with the data of respondents we can know that the alternatives that are compared having their priorities different. Based on the above test had employees who are entitled to a bonus that employee A and C whereas with methods that are in use by the company employees get bonus is employee E.Keyword: decision, motivation, criteria